CHARACTERIZATION OF SCAFFOLDING BASED ON THE STUDENTS’ THINKING ERROR IN SOLVING MATHEMATIC PROBLEM - Anton Prayitno; Efi Fatma Nurjana; Fitria Khasanah (Jurnal Kependidikan, 2017)
This study was aimed at identifying the thinking error of the students in solving mathematics problems and providing the scaffolding. The study was descriptive explorative. This study was conducted in Mojokerto.The subjects were 25 students, however, only 3 were described since the scaffolding used was of level 2. Data were collected initially by asking the subjects to solve mathematic test items. Error patterns were identified from the students’ works. The students who made errors were chosen as the research subjects. Findings show that there were differences in the students’ thinking patterns before and during the provision of scaffolding. These differences occur due to the different scaffolding treatments according to the thinking errors. For students who have difficulties in understanding problems, the scaffolding is in the form of leading questions. For those who have difficulties in connecting previous concepts, the scaffolding is in the form of drawing tables and recalling previous materials. For students who have difficulties in organizing a strategy, the scaffolding is in the form of recalling the strategy that has been plannedKARAKTERISASI SCAFFOLDING BERDASARKAN KESALAHAN BERPIKIR SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA Penelitian ini bertujuan untuk mengidentifikasi kesalahan berpikir siswa dalam menyelesaikan masalah matematika dan pemberian scaffolding. Penelitian menggunakan metode deskriptif eksploratif. Penelitian dilakukan di beberapa sekolah di Kota Mojokerto. Subjek penelitian ini berjumlah 25 orang, namun yang dipaparkan pada artikel hanya 3 dengan scaffolding level 2. Prosedur pengumpulan data diawali dengan siswa diminta untuk menyelesaikan masalah matematika. Selanjutnya, hasil pekerjaan tersebut diidentifikasi pola kesalahannya. Siswa yang menghasilkan pekerjaan salah, dijadikan subjek penelitian. Hasil penelitian menunjukkan adanya perbedaan berpikir siswa sebelum pemberian scaffolding dan selama pemberian scaffolding. Perbedaan terjadi karena peneliti memberikan scaffolding sesuai jenis kesalahan berpikir yang dialami siswa. Ketika subjek mengalami kesulitan dalam memahami masalah, scaffolding yang diberikan berupa pertanyaan arahan. Apabila subjek mengalami kesulitan dalam menghubungkan dengan konsep terdahulu, scaffolding berupa petunjuk untuk membuat tabel dan mengingat kembali materi yang telah dipelajari. Untuk subjek yang mengalami kesulitan dalam menyusun strategi, scaffolding berupa dorongan untuk mengingat kembali strategi yang sudah direncanakan